TECHNIKI OBRAZOWANIALeft ventricular non-compaction: an increasingly diagnosed cardiomyopathy - Miszalski-Jamka, Karol; Głowacki, Jan; Kalarus, Zbigniew (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
The number of diagnosed cases of left ventricular non-compaction (LVNC) has increased for the last two decades. Recently, LVNC has become the subject of interest of many scientists groups. The knowledge on this subject needs updating. Left ventricular non-compaction is also defined as spongy cardiomyopathy. Characteristic feature of LVNC is a presence of non-compacted, this is hipertrabeculated myocardium of the left ventricle. The authors discuss the epidemiology and the genetic mechanisms leading to this disease. Diagnosing of LVNC in clinical practice is based on TTE (transthorasic echocardiography) and on cardiac magnetic resonanse. The other methods as: contrast echocardiography, computed tomography or angiography are rare. The essential diagnostic task is to distinguish between the patients with LVNC and with hipertrabeculation of the left ventricle as a norm variant. The spectrum of clinical symptoms is very wide – form totaly asymptomatic patients to the patients requiring heart transplantation. The decreased tolerance of effort, dyspnea, non-specific chest pain/discomfort, palpitation, syncope or embolic complications are the most frequent symptoms. Circulatory insufficiency, arrhythmia and systemic embolic complications are classic triad complications. In some patients the prognosing is poor; heart transplantation or cardiac death in that population are frequent. There is a need of study in bigger patients cohorts to recognise many controversial problems, e.g. to distinguish genotype- fenotype correlation, to find a real number of complications and to estimate optimal ways of treatment.